2019
DOI: 10.3390/ijms20123087
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of gga-miR-451 by AhR:Arnt in Mycoplasma gallisepticum (HS Strain) Infection

Abstract: MicroRNAs (miRNAs) have been determined to be important regulators for pathogenic microorganism infection. However, it is largely unclear how miRNAs are triggered during pathogen infection. We previously reported that the up-regulation of gga-miR-451 negatively regulates the Mycoplasma gallisepticum (MG)-induced production of inflammatory cytokines via targeting tyrosine3-monooxygenase/tryptophan5-monooxygenase activation protein zeta (YWHAZ). The aim of this study was to investigate the mechanism regulating g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…It is worth mentioning that gga-miR-451 regulates the MG-induced production of inflammatory cytokines via targeting YWHAZ (16). Moreover, our previous study also confirmed that AhR:Arnt bind to the gga-miR-451 promoter and facilitate gga-miR-451 transcription in DF-1 cells (17).…”
supporting
confidence: 72%
“…It is worth mentioning that gga-miR-451 regulates the MG-induced production of inflammatory cytokines via targeting YWHAZ (16). Moreover, our previous study also confirmed that AhR:Arnt bind to the gga-miR-451 promoter and facilitate gga-miR-451 transcription in DF-1 cells (17).…”
supporting
confidence: 72%
“…There is a growing appreciation of the role of the melatonergic pathway, including within mitochondria and the cytoplasm, in the regulation of mitochondrial function, which may be particularly important in immune cells [ 25 ]. The AhR can regulate the melatonergic pathway via a number of mechanisms, including 1) the induction of CYP1A1 and CYP1B1, with CYP1A1 increasing the metabolism of estrogen, whilst CYP1B1 leads to the ‘backward’ conversion of melatonin to its precursor, NAS, and thereby increasing the NAS/melatonin ratio [ 26 ]; and 2) AhR suppression of YWHAZ (14-3-3ζ/δ) [ 8 ], given that 14-3-3ζ/δ is necessary to stabilize the initial enzyme in the melatonergic pathway AANAT. As the autocrine effects of melatonin are necessary for immune cells to switch from an M1-like pro-inflammatory phenotype to an M2-like phenotype [ 27 ], AhR activation, via inhibition of the melatonergic pathway, would be expected to contribute to a prolongation of the ‘cytokine storm’.…”
Section: Sars-cov-2 Entry and Pathophysiologymentioning
confidence: 99%
“…Consequently, an increase in kynurenine production and activation of the AhR is associated with a decrease in serotonin and melatonin. AhR activation, via cytochrome P450 (CYP) 1B1, may also lower melatonin availability, as will the AhR suppression of YWHAZ (14-3-3ζ/δ) [ 8 ], which is required to stabilize the first enzyme in the melatonergic pathway, aralkylamine N-acetyltransferase (AANAT). It is proposed that AhR activation and associated suppression of pineal and immune cell melatonin, coupled to the AhR’s suppression of acetyl-coenzyme A (CoA) and specialized pro-resolving mediators (SPMs), are crucial in driving the heightened cytokines underpinning the ‘cytokine storm’ as well as suppressing the endogenous anti-viral response.…”
Section: Introductionmentioning
confidence: 99%
“…Such trophic effects of NAS may arise from any of the cells forming the tumour microenvironment, including NK cells and CD8+ t cells. As 14-3-3ζ/δ (YWHAZ) is crucial for AANAT stabilisation, the AhR inhibition of14-3-3ζ/δ [ 19 ], including via microRNAs, allows the AhR to suppress both NAS and melatonin production. As the melatonergic pathway seems to be evident in the cytoplasm and mitochondria of all investigated cells, the AhR may therefore exert some of its effect in different cellular compartments via melatonergic pathway regulation.…”
Section: Tumour Microenvironment and Immune Suppression: Exhaustiomentioning
confidence: 99%